Rattan (Calamus spp.) gardens of Kalimantan: resilience and evolution in a managed non-timber forest product system - Pambudhi, F.; Belcher, B.; Levang, P.; Dewi, S. (Center for International Forestry Research, 2004)
Rattan cultivated as part of the traditional swidden agricultural system has been a major source of internationally traded rattan raw material and, more recently, the basis of a strong domestic furniture and handicrafts industry. The rattan gardens of Kalimantan provide an example of an intermediate non-timber forest product management system that is well adapted to the local economy and ecology. Over the past two decades, however, important changes have taken place, changes that tested the resilience of the system. Government policies designed to encourage the domestic processing industry and monopsonistic manufacturing association have sharply depressed demand and prices. New developments in the region, in the form of roads, industrial plantations, mining, and other new activities. Recent widespread forest fires have destroyed large areas of rattan gardend, effectively forcing some rattan farmers out of businnes. Under current conditions, withlow prevailing demand and prices, rattan gardens provide valuable ecological services, in term of biodiversity conservation and other forest functions. As rattan remains an important commodity in Indonesia and internationally, the rattan garden system may remain viable, at least in the medium term.